Pendidikan Multikultural Dalam Menumbuhkan Sikap Toleransi Antara Siswa Berbeda Agama - Lina Ruba (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2024)
This study aims to determine the process of implementing multicultural education and to determine supporting and inhibiting factors in realizing inter-religious harmony in SMA Negeri 1 Raijua. The subjects of this study are principals, Christian teachers, and students. The data are collected through observation, interviews, and documentation. The study shows that multicultural education in SMA Negeri 1 Raijua has been implemented well. The students have understood, applied, and been tolerant of differences, especially in religion, ethnicity, tribe, culture, race, and school environment. These can provide a good example, instil a humanitarian attitude in the school environment and surroundings through community service, and foster a spirit of togetherness that creates social sensitivity in every student. The process of multicultural education is also carried out through the example of teachers and students through the subject contained in the curriculum. Supporting factors for the multicultural education process are the school environment, school curriculum, and infrastructure. The inhibiting factors of the multicultural education process are the lack of supporting media, the lack of posters that contain multicultural values, and the lack of multicultural education practices outside the school.